The Translation of the Songs in Disney’s Beauty and the Beast: An Example of Manipulation - Lucía Loureiro Porto (Miscelánea: A Journal of English and American Studies, 2002)
The aim of this paper is to analyse the translation of the songs in Disney’s Beauty and the Beast taking into account translation norms as defined by Toury (1995). The paper is divided into two main parts. The first part reviews some works on Translation Studies and manipulation theory, as our theoretical framework or background for the corpus-based part of the paper. The translation shows important regularities in the shifts brought about by cultural differences between the source and the target community, as well as those that reveal some kind of manipulation of the text towards a more naïve presentation. Examples of shift such as substitution material (concrete for abstract vocabularity, for instance) or total deletion of all traces of slang/vulgar language are provided as evidence of a rather standardised and conventional translation. In view of this evidence, it is hypothesized that the translator’s intention might have been to make the text more suitable for children, even though the original text was intended for a wider audience.